Stimulant properties of bromocriptine on central dopamine receptors in comparison to apomorphine, (+)-amphetamine and L-DOPA. - Johnson, A M (1976)
1. The activity of bromocriptine has been investigated in tests for the stimulation of central dopaminergic mechanisms. The results obtained have been compared with those of apomorphine, (+)-amphetamine and L-DOPA. 2. Bromocriptine (2.5 to 10 mg/kg) induced stereotyped sniffing and licking in rats. The stereotypy was more intense than that induced by L-DOPA and less intense than that of apomorphine and (+)-amphetamine over the dose ranges studied. 3. In rats lesioned unilaterally in the substantia nigra by local injection of 6-hydroxydopamine, bromocriptine, like apomorphine and L-DOPA, induced turning contralateral to the side of the lesion. The smallest dose of bromocriptine to induce turning was 0.5 mg/kg. 4. Reserpine-induced catalepsy in mice was antagonized by bromocriptine, with an ED50 of 1.8 mg/kg. It was intermediate in potency to apomorphine and L-DOPA. 5. Spontaneous locomotor activity in mice was stimulated by bromocriptine in a dose-dependent manner from 2.5 to 10 mg/kg after an initial suppression of activity. 6. In all experiments, bromocriptine was characterized by a prolonged duration of activity after a delay in the onset of effect. 7. The stereotyped behaviour induced by bromocriptine was inhibited by prior administration of pimozide, reserpine or alpha-methyl-p-tyrosine. 8. Bromocriptine-induced turning behaviour was abolished by pretreatment with pimozide, and reduced after alpha-methyl-p-tyrosine treatment. 9. The results obtained support the conclusion that bromocriptine acts by stimulating dopamine receptors in the central nervous system and that intact catecholamine synthesis and granular amine storage mechanisms are necessary for it to bring about its effects.